Resilience and patience (sabr) in Islamic view when observing the movement control (order MCO) during the covid 19 pandemic - Salleh, Kamarudin; Rahman, Z, Ab; Noor, A.Y., Mohd; M.I.A.M., Kashim; Sunawari Long, Ahmad; Zaki Hasan, Ahmad; Rahim Ridzuan, Abdul; Ismail, Shafinar; Hanin Hamjah, 9Salasiah; Najib Abdul Kadir, Muhd; Zarrina Saari, Che; Farid, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The study examined the relationship of resilience and patience (sabr) in Islamic view when observing the movement control (order MCO) during the COVID 19 pandemic. Resilience means the ability to survive by recovering from a situation or returning to its original shape after been compressed, stretched or bent. When the term resilience is used in psychology it means a person’s ability to quickly recover from changes, sickness, accidents, or adversities. Ibnu Qayyim al-Jawziyyah (1292-1350) opined that patience is the withholding of natural inclinations to avoid inappropriate occurrences, withholding from complaining and withholding oneself (body) from doing something negative, such as slapping one’s own face or tearing one’s clothes when something unfortunate happens. Patience has a positive relationship with resilience, which translates to not giving up easily when faced with a dire situation. This is indicated in another study (Herman, 2015), which suggested that internal factors do strongly influence an individual’s resilience.